2017
DOI: 10.1364/ao.56.006649
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical localization of blood vessels and 3D printing for guiding oral surgery

Abstract: Diffuse optical imaging through centimeters of tissue has emerged as a powerful tool in biomedical research. However, applications in the operating theater have been limited in part due to data set requirements and computational burden. We present an approach that uses a small number of optical source-detector pairs that allows for the fast localization of arteries in the roof of the mouth and has the potential to reduce complications during oral surgery. The arteries are modeled as multiple-point absorbers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…These analytical solutions to the diffusion equation subject to boundary conditions have been shown to match Monte Carlo simulations [24] and experiments of photon propagation in highly scattering media [19]. It has been shown that small fluorescent inhomogeneities can be well approximated as point emitters because of the rapid attenuation of high spatial frequencies in scattering media [10], [19], [20], [25]. For this reason, imaging based on a point representation is possible.…”
Section: Forward Model For a Single Fluorescent Emittermentioning
confidence: 78%
See 3 more Smart Citations
“…These analytical solutions to the diffusion equation subject to boundary conditions have been shown to match Monte Carlo simulations [24] and experiments of photon propagation in highly scattering media [19]. It has been shown that small fluorescent inhomogeneities can be well approximated as point emitters because of the rapid attenuation of high spatial frequencies in scattering media [10], [19], [20], [25]. For this reason, imaging based on a point representation is possible.…”
Section: Forward Model For a Single Fluorescent Emittermentioning
confidence: 78%
“…Pacemaking neurons, which fire periodically at 2-3 Hz [47], may also prove useful for verification or for further constraining the methods. Absorption instead of fluorescent emitters could be localized [20], and the forward model could incorporate multiple point absorbers or emitters instead of just one [25]. There are other biomedical applications, such as the extraction of kinetic information [48], [49], as well as other physical problems where fast localization benefits the extraction of physical information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascularization assessment during of organ and tissue reconstruction. DOS can visualize arteries in angiosurgical and plastic operations [69,70]. In the recent literature, a great number of reports describe successful results of DOS monitoring of superficially located skin fascial flaps used in breast reconstruction with tissue oxygenation assessment to the depth of 5-12 mm [71][72][73][74].…”
Section: Diffuse Optical Spectroscopymentioning
confidence: 99%